Augustine on Manichaeism and Charisma - Kaufman, Peter Iver 1946- (2012)
Augustine was suspicious of charismatics’ claims to superior righteousness, which supposedly authorized them to relay truths about creation and redemption. What follows finds the origins of that suspicion in his disenchantment with celebrities on whom Manichees relied, specialists whose impeccable behavior and intellectual virtuosity were taken as signs that they possessed insight into the meaning of Christianity’s sacred texts. Augustine’s struggles for self-identity and with his faith’s intelligibility during the late 370s, 380s, and early 390s led him to prefer that his intermediaries between God and humanity be dead (martyred), rather than alive and charismatic.
Keywords: Augustine; Faustus; Mani; Manichaeism; arrogance; Charisma; Esotericism; Truth